Enhancing Work Motivation Through Transformational Leadership and Change Readiness in Health Workers During Digital Era Transitions - Ellynia Ellynia; Andrianto Widjaja; yarwin yari; Khalida Ziah Sibualamu; Rizqa Wahdini; Sarah Geltri Harahap (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Digital transformation in healthcare requires adaptive leadership and a workforce equipped to navigate ongoing organizational change. This study investigates the relationship between transformational leadership, readiness for change, and work motivation among healthcare professionals in Indonesia. A cross-sectional quantitative design was employed, involving 216 participants from five private hospitals selected through purposive sampling. Data were collected using a validated questionnaire assessing transformational leadership, readiness for change, and work motivation, and analyzed using Spearman's rank correlation. Findings revealed that most respondents perceived transformational leadership at a moderate level, exhibited high readiness for change, and reported moderate to high levels of work motivation. Significant positive correlations were identified between transformational leadership and work motivation (r = 0.501; p < 0.001), transformational leadership and readiness for change (r = 0.528; p < 0.001), and between work motivation and readiness for change (r = 0.647; p < 0.001)These results underscore the pivotal role of transformational leadership in enhancing employee motivation and fostering change readiness within healthcare settings. Strengthening leadership competencies, particularly in inspirational motivation, individualized consideration, and intellectual stimulation, is vital for the successful implementation of digital transformation initiatives. The study highlights the importance of structured leadership development and institutional support in cultivating a motivated, adaptable, and innovation-oriented healthcare workforce. Keyword: Digital Transformation, Healthcare Workforce, Readiness To Change, Transformational Leadership, Work Motivation